Massive xanthomatosis and altered composition of atherosclerotic lesions in hyperlipidemic mice lacking acyl CoA:cholesterol acyltransferase 1 - Accad, Michel (American Society for Clinical Investigation, 2000)
Inhibitors of acyl CoA:cholesterol acyltransferase (ACAT) have attracted considerable interest as a potential treatment for atherosclerosis. Currently available inhibitors probably act nonselectively against the two known ACATs. One of these enzymes, ACAT1, is highly expressed in macrophages in atherosclerotic lesions, where it contributes to foam-cell formation. In this study, we examined the effects of selective ACAT1 deficiency in two mouse models of atherosclerosis. In the setting of severe hypercholesterolemia caused by deficiency in apoE or the LDL receptor (LDLR), total ACAT1 deficiency led to marked alterations in cholesterol homeostasis and extensive deposition of unesterified cholesterol in the skin and brain. Bone marrow transplantation experiments demonstrated that ACAT1 deficiency in macrophages was sufficient to cause dermal xanthomas in hyperlipidemic LDLR-deficient mice. ACAT1 deficiency did not prevent the development of atherosclerotic lesions in either apoE-deficient or LDLR-deficient mice, despite causing relatively lower serum cholesterol levels. However, the lesions in ACAT1-deficient mice were atypical in composition, with reduced amounts of neutral lipids and a paucity of macrophages in advanced lesions. Although the latter findings may be associated with increased lesion stability, the marked alterations in cholesterol homeostasis indicate that selectively inhibiting ACAT1 in the setting of severe hyperlipidemia may have detrimental consequences.